The Influence of Knowledge and Family Role on Reproductive Health Maintenance Behavior Among Early Adolescent Girls - Rani Cahya; Vicky Arfeni Warongan; Melisa Anggryani; Debora Kresya Pane; Sri Wulan Dari (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the relationship between knowledge and family role with reproductive health maintenance behavior among early adolescent girls at MIS Al-Kautsar Medan Johor in 2025. Early adolescence is a critical developmental period during which young girls experience significant physiological and psychological changes, making proper reproductive health practices essential. Despite this, many adolescents still lack adequate knowledge and receive insufficient family support, contributing to poor hygiene behaviors. Materials and methods. This study employed a quantitative analytical design with a cross-sectional approach. A total of 44 early adolescent girls aged 11–12 years were selected as respondents. Data were collected using structured questionnaires measuring reproductive health knowledge, family role, and reproductive health behavior. Descriptive statistics were used to describe respondents’ characteristics and variable distributions. Bivariate analysis using the Chi-Square test was performed to determine the relationship between independent and dependent variables. Results. The findings showed that 63.6% of respondents had poor knowledge, 72.7% experienced low family support, and 56.8% demonstrated poor reproductive health behavior. Chi-Square analysis revealed a significant relationship between knowledge and reproductive health behavior (χ² = 10.53; p = 0.001). Family role was also significantly associated with reproductive health behavior (χ² = 13.41; p = 0.000). Adolescents with good knowledge and strong family involvement were more likely to practice proper reproductive hygiene. Conclusions. Both knowledge and family role significantly influence reproductive health maintenance behavior among early adolescent girls. Strengthening reproductive health education in schools and enhancing family involvement are essential strategies for improving adolescents’ hygiene practices. Collaborative efforts between educators, parents, and health professionals—particularly midwives—are needed to support early adolescents in developing healthy reproductive habits.